Remote school instruction in Fall 2020 and psychiatric emergencies among adolescents in Los Angeles County - Shutong Huo; Annie Ro; Senxi Du; Andrew Young; Tim A. Bruckner (BMC Psychiatry)
Abstract Objective Schools play an essential role in providing mental health care for adolescents. School closures during COVID-19, as well as re-opening to remote-only instruction in Fall 2020, may indirectly affect the utilization of emergency psychiatric care. We examine COVID-19-related changes in emergency psychiatric care among youth during the school closure and after school reopening (with remote instruction). Methods We use Box-Jenkins interrupted time series methods to analyze psychiatric emergency department (ED) visits among patients 10–19 years at LAC + USC Medical Center (LAC + USC) between January 5th, 2018, and December 31st, 2020. We control for the 1st societal shutdown in LA County (i.e., the nine weeks from March 13 to May 14, 2020) when analyzing the potential “return to remote school” shock. Results Youth psychiatric ED visits fell by 15.3 per week during the Spring 2020 school closure (p < .05). The “return to remote school” coefficient (i.e., August 14th to September 10, 2020), by contrast, is positive but does not reach statistical detection above expected values (p = .11). However, the proportion of psychiatric ED visits rises 38% among youth during the “return to remote school” period (p = 0.006). Conclusion The initiation of Fall 2020 remote instruction corresponded with a greater proportion of youth ED visits that are classified as psychiatric.